2016
DOI: 10.1016/j.taap.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Equol inhibits growth, induces atresia, and inhibits steroidogenesis of mouse antral follicles in vitro

Abstract: Equol is a non-steroidal estrogen metabolite produced by microbial conversion of daidzein, a major soy isoflavone, in the gut of some humans and many animal species. Isoflavones and their metabolites can affect endogenous estradiol production, action, and metabolism, potentially influencing ovarian follicle function. However, no studies have examined the effects of equol on intact ovarian antral follicles, which are responsible for sex steroid synthesis and further development into ovulatory follicles. Thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…Previous studies with genistein, a commonly used phytoestrogen found in soy, showed that it could induce atresia of rat follicles [34] and inhibit growth of mouse antral follicles via Cdkn1a upregulation [35]. Equol, a metabolite of the soy phytoestrogen daidzein, was found to inhibit mouse antral follicle growth and increase follicle atresia [36]. The isoliquiritigenin-induced inhibition of follicle growth in the present study may thus potentially be due to disruption of cell cycle regulators causing cell cycle arrest, increased apoptosis causing follicle atresia, or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with genistein, a commonly used phytoestrogen found in soy, showed that it could induce atresia of rat follicles [34] and inhibit growth of mouse antral follicles via Cdkn1a upregulation [35]. Equol, a metabolite of the soy phytoestrogen daidzein, was found to inhibit mouse antral follicle growth and increase follicle atresia [36]. The isoliquiritigenin-induced inhibition of follicle growth in the present study may thus potentially be due to disruption of cell cycle regulators causing cell cycle arrest, increased apoptosis causing follicle atresia, or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found to decrease estradiol levels in porcine granulosa cells [44]. Equol was found to inhibit the production of estradiol, testosterone, and progesterone by mouse antral follicles in vitro [36]. Daily consumption of soy products containing genistein and daidzein for one month reduced circulating plasma levels of estradiol and progesterone in healthy, premenopausal women [42].…”
Section: Discussionmentioning
confidence: 99%
“…One in vitro study showed that equol decreased the mRNA expression of CYP11A1, a key enzyme in the conversion of cholesterol to pregnenolone. As pregnenolone is the steroid precursor of testosterone, the downregulation of CYP11A1 reduced the production of testosterone in an in vitro ovarian follicle culture system [16]. Additionally, equol directly diminished the ability of antral follicles to produce testosterone by increasing the ratio of Bax to Bcl2 mRNA in these follicles and thus dysregulating the apoptotic pathway [16].…”
Section: Discussionmentioning
confidence: 99%
“…As pregnenolone is the steroid precursor of testosterone, the downregulation of CYP11A1 reduced the production of testosterone in an in vitro ovarian follicle culture system [16]. Additionally, equol directly diminished the ability of antral follicles to produce testosterone by increasing the ratio of Bax to Bcl2 mRNA in these follicles and thus dysregulating the apoptotic pathway [16]. Equol also inhibited the secretion of testosterone from antral follicles by reducing the levels of estrogens, thus inhibiting the production of cyclic adenosine monophosphate [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation